2020
DOI: 10.3390/jcm9092901
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Spacer Exchange in Two-Stage Exchange Arthroplasty for Periprosthetic Joint Infection?

Abstract: Periprosthetic joint infection (PJI) continues to be one of the most serious complications after hip and knee arthroplasty. The choice of surgical treatment depends on a multitude of factors like chronicity of infection, host factors, and institutional or surgeon experience. Two-stage exchange remains one of the most commonly used technique for chronic PJI in the United States of America. The intended two-stage revision may involve an additional interim procedure where the initial antibiotic cement spacer is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…In contrast to this findings, previous studies have shown that positive cultures during the second stage are associated with a higher failure rate 25,26 . Therefore, if there are evidently signs of persistent spacer infection preoperatively or intraoperatively, reimplantation of an implant seems precarious and spacer exchange should be performed 27 …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast to this findings, previous studies have shown that positive cultures during the second stage are associated with a higher failure rate 25,26 . Therefore, if there are evidently signs of persistent spacer infection preoperatively or intraoperatively, reimplantation of an implant seems precarious and spacer exchange should be performed 27 …”
Section: Discussionmentioning
confidence: 79%
“… 25 , 26 Therefore, if there are evidently signs of persistent spacer infection preoperatively or intraoperatively, reimplantation of an implant seems precarious and spacer exchange should be performed. 27 …”
Section: Discussionmentioning
confidence: 99%
“…One or multiple ALCS exchanges between the first-stage surgery and the final prosthesis insertion are reported in 12-17% of patients with PJI [ 62 , 76 , 78 ].…”
Section: Reviewmentioning
confidence: 99%
“…Spacer exchange is dictated by mechanical causes or because of persisting infection [ 62 ]. Mechanical causes of spacer replacement are the risk of wound or skin compromise secondary to pressure, compression of nerves or vessels and, finally, pain and discomfort from a dislocated spacer.…”
Section: Reviewmentioning
confidence: 99%
“…Secondly, Kozaily et al tried to examine a place for an additional spacer intervention (i.e., the initial antibiotic cement spacer is removed and a new spacer is inserted) during two-stage PJI treatment [18]. There may be mechanical and biological reasons for a spacer to be exchanged.…”
mentioning
confidence: 99%